POTENSI KRONIK SEJARAH SUMATRA KARYA WILLIAM MARSDEN SEBAGAI SUMBER BELAJAR SEJARAH - Syah, Edwin Fitria; Wijaya, Daya Negri (Jurnal Pendidikan Sejarah Indonesia, 2025)
Abstract: The Chronicle of Sumatra History by William Marsden is one of the historical sources that is included in the primary sources in the form of notes that can be used as a source for learning history. This study aims to determine and analyze the chronicle of the History of Sumatra by William Marsden which is used to enrich the history learning sources for high school students, as well as to determine the relevance of the use of the chronicle of the History of Sumatra by William Marsden with the Merdeka Curriculum. This study uses a descriptive analytical method with a qualitative approach. In writing, the researcher used several books and journals that were relevant and in accordance with the topic of discussion written. The results and discussion of this study, the chronicle of the History of Sumatra is a note from William Marsden and was later published as a book. The chronicle presents various information about the history of Sumatra as well as the geographical conditions, natural resources, social, cultural, political, and government of the Sumatran people in the 18th century, which helps students understand the diversity of Indonesian culture. The Chronicle of the History of Sumatra also has relevance to the Merdeka Curriculum phase F. This book can fulfill the elements of the CP history phase F, including being relevant to the material on the history of colonialism and imperialism in Indonesia, developing historical literacy and historical research. This book can also help students develop historical thinking and use primary sources of history, as well as provide reinforcement of nationalism over the richness and diversity of the Indonesian nation.